2017
DOI: 10.1016/j.jhep.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline hepatotoxicity: Clinical characterization and identification of HLA-B∗35:02 as a risk factor

Abstract: Background & Aims Minocycline hepatotoxicity can present with prominent autoimmune features in previously healthy individuals. The aim of this study was to identify genetic determinants of minocycline DILI in a well-phenotyped cohort of patients. Methods Caucasian patients with minocycline DILI underwent genome-wide genotyping and were compared to unexposed population controls. Human leukocyte antigen (HLA) binding of minocycline was assessed using AutoDock Vina. Results Amongst the 25 cases, 80% were fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 36 publications
2
75
0
1
Order By: Relevance
“…Genetic variants in the IL28 gene were highly predictive of response to interferon therapy in patients with chronic hepatitis C. (5) Variations in the HLA region are a well-known risk factor for liver injury due to antibacterial agents such as flucloxacillin, amoxicillin-clavulanate, or minocycline. (6)(7)(8)(9) However, pharmacogenomics research within the NAFLD area is somewhat limited. One study showed that genetic variation in cytochrome P450 4F2 was not a significant predictor of response to vitamin E in nondiabetic patients with biopsy-proven NASH.…”
mentioning
confidence: 99%
“…Genetic variants in the IL28 gene were highly predictive of response to interferon therapy in patients with chronic hepatitis C. (5) Variations in the HLA region are a well-known risk factor for liver injury due to antibacterial agents such as flucloxacillin, amoxicillin-clavulanate, or minocycline. (6)(7)(8)(9) However, pharmacogenomics research within the NAFLD area is somewhat limited. One study showed that genetic variation in cytochrome P450 4F2 was not a significant predictor of response to vitamin E in nondiabetic patients with biopsy-proven NASH.…”
mentioning
confidence: 99%
“…More recently, Nicoletti et al demonstrated that HLA‐A * 33:01 was a risk factor for cholestatic and mixed DILI in Caucasians from a number of drugs, including terbinafine, fenofibrate and ticlopidine . Finally, we recently showed that HLA‐B *35:02 was over‐represented in Caucasian patients with minocycline hepatotoxicity . However, due to the small number of minocycline cases, replication cohorts are needed to confirm the value of testing for this allele in minocycline‐treated patients presenting with liver injury.…”
Section: Genetic Biomarkersmentioning
confidence: 89%
“…21 Finally, we recently showed that HLA-B *35:02 was over-represented in Caucasian patients with minocycline hepatotoxicity. 84 However, due to the small number of minocycline cases, replication cohorts are needed to confirm the value of testing for this allele in minocycline-treated patients presenting with liver injury.…”
Section: G Ene Ti C B I Omark Er Smentioning
confidence: 99%
“…Urban et al recently demonstrated that individuals who are HLA-B*35:02 carriers are at increased risk of developing minocycline-related liver injury. 8 Re-exposure to hepatotoxic drugs is strongly discouraged, particularly if there is a significant rise in transaminases (>5× upper limit of normal) or jaundice. 3 In our case, an adverse drug reaction report was completed, and she was advised to avoid tetracyclines for life.…”
Section: Discussionmentioning
confidence: 99%